Towards human factor taxonomy with cognitive generic terms - Baziuk, Pedro Alejandro (2014)
In this paper one of the most important issues in human reliability analysis: human error taxonomies will be briefly described divided in two categories: 11 classical and 6 modern taxonomies. Aspects focused on the development of these approaches differ widely among classic and modern taxonomies. The two desirable features sought in newest taxonomies (interrater reliability and generality) seem to be contradictory to each other. Also the most important issues will be summarized. The analysis of the review points out that several taxonomies could be applied in some adverse scenario and suggests that possibly the idea of failure taxonomic should be discarded and replaced by human factor taxonomy with cognitive generic terms.